Rica em espécies, mas defaunada: o caso dos mamíferos de médio e grande porte de uma área protegida na Amazônia - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
Neotropical medium and large-bodied mammals constitute key elements in forest ecosystems, and Protected Areas (PAs) are essential for their conservation. In Brazil, the Sustainable Use Protected Areas (SU-PAs) are a subgroup of PAs that allows both the conservation of biodiversity and the sustainable exploration of natural resources. SU-PAs offer a great opportunity for conserving medium and large-bodied mammals because of their large size, especially in the Amazon. However, SU-PAs are usually affected both by internal and external pressures, and different parts of the same SU-PA may have distinct degrees of defaunation (i.e., local or functional extinction of animals). We sampled mammals using camera traps in two areas with distinct histories of human occupation in the Tapajós National Forest (TNF), and show differences in species richness, assemblage structure, number of records per species, and levels of defaunation. A compilation of other studies conducted in similar sites of the TNF suggest that human activities may have driven populations of some large-bodied mammal species, such as the tapir (Tapirus terrestris) and white-lipped peccary (Tayassu pecari) to very low levels in the TFN, and that compensation by large rodents may have occurred in the defaunated area. Local differences in human occupation within and between PAs are common in the Amazon, which demands area-specific actions from public authorities to minimize impacts on wildlife caused by both legal or illegal activities.
Keywords: Armadilha Fotográfica; Mamíferos; Caça Furtiva; Floresta Tropical; Manejo; Vida Selvagem.; CNPQ::CIÊNCIAS BIOLÓGICAS